Development of small signal amplifiers in the frequency range 4 GHz to 8 GHz using Gallium arsenide field effect transistors. - Nortierr, Johannes Richard (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1981.